2019
DOI: 10.18176/jiaci.0385
|View full text |Cite
|
Sign up to set email alerts
|

Benralizumab: A New Approach for the Treatment of Severe Eosinophilic Asthma

Abstract: Eosinophilic asthma is the most common phenotype of severe asthma. It is characterized by abnormal production and release of type 2 cytokines from T helper type 2 (T H 2) lymphocytes and type 2 innate lymphoid cells, such as IL-5. This leads to a persistent increase and activation of eosinophils in blood and the airways despite treatment with high-dose inhaled corticosteroids. Eosinophil differentiation, survival, and activation are preferentially regulated by IL-5, a cytokine that binds to the IL-5 receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 59 publications
1
33
0
2
Order By: Relevance
“…Several phase 3 RCT have recently shown that, as add-on treatment of severe eosinophilic asthma, benralizumab is characterized by an excellent pattern of efficacy, safety, and tolerability (Pelaia et al, 2018b,c;Gonzalez et al, 2019). In particular, CALIMA and SIROCCO trials showed that benralizumab significantly decreased the annual rate of severe eosinophilic exacerbations of asthma, and also improved asthma symptom control and enhanced FEV 1 (Bleecker et al, 2016;FitzGerald et al, 2016).…”
Section: Il-5 and Its Receptor: Molecular Targets For Biological Thermentioning
confidence: 99%
“…Several phase 3 RCT have recently shown that, as add-on treatment of severe eosinophilic asthma, benralizumab is characterized by an excellent pattern of efficacy, safety, and tolerability (Pelaia et al, 2018b,c;Gonzalez et al, 2019). In particular, CALIMA and SIROCCO trials showed that benralizumab significantly decreased the annual rate of severe eosinophilic exacerbations of asthma, and also improved asthma symptom control and enhanced FEV 1 (Bleecker et al, 2016;FitzGerald et al, 2016).…”
Section: Il-5 and Its Receptor: Molecular Targets For Biological Thermentioning
confidence: 99%
“…The best known pathogenic mechanism involved in severe asthma development is mediated by eosinophils and IL-5 [6]. New anti-eosinophilic monoclonal antibodies, mepolizumab and benralizumab, have recently been approved to reduce exacerbations and to improve lung function in patients with severe and uncontrolled asthma with eosinophilic inflammation [7-9]. The 2 drugs have different mechanisms of action: mepolizumab blocks the activity of circulating cytokine IL-5 and benralizumab interferes with the IL-5 receptor alpha (IL-5Rα) of eosinophils [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Since her airway and ear inflammation might be related to type 2 inflammation and her IgE level was low, anti-IL-5 biologic therapy was selected for the add-on therapy as recommended by GINA [ 1 ]. Benralizumab, an monoclonal antibody to IL-5 receptor α (IL-5Rα) on eosinophils and also binds the RIIIa region of the FCγ receptor (FcγRIIIa) on natural killer cells, macrophages and neutrophils with a high affinity [ 23 ], was used in our case, and nearly complete depletion of eosinophils in the peripheral blood was achieved through enhanced antibody-dependent cell-mediated cytotoxicity [ 24 ]. Following depletion of eosinophils in the peripheral blood, asthma control, asthma-related QOL, and pulmonary function dramatically improved in a month ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…This antibody also binds to the FcγRIIIa receptor on natural killer cells, macrophages, and neutrophils, inducing antibody-dependent cellular cytotoxicity to eosinophils. This double-function, which is different from other IL-5 antagonist such as mepolizumab and reslizumab [ 23 ], might have induced the near-complete deletion of eosinophils from the patient's airways and provided rapid symptomatic relief. Although therapy with anti-IL-5 antibodies are greatly effective for treating type 2 inflammation by suppressing eosinophilic infiltration [ 23 , 24 ], the bottle neck of using these drugs is the high cost of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation